2016
DOI: 10.5337/2016.213
|View full text |Cite
|
Sign up to set email alerts
|

Business models for fecal sludge management.

Abstract: Resource Recovery and Reuse (RRR) is a subprogram of the CGIAR Research Program on Water, Land and Ecosystems (WLE) dedicated to applied research on the safe recovery of water, nutrients and energy from domestic and agroindustrial waste streams. This subprogram aims to create impact through different lines of action research, including (i) developing and testing scalable RRR business models, (ii) assessing and mitigating risks from RRR for public health and the environment, (iii) supporting public and private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…In its approach to business models and the analysis undertaken, this report is based on a previous study conducted by Rao et al (2016). The key findings from Part A are summarized below:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In its approach to business models and the analysis undertaken, this report is based on a previous study conducted by Rao et al (2016). The key findings from Part A are summarized below:…”
Section: Discussionmentioning
confidence: 99%
“…Although lack of data over a significant time period precludes detailed analysis, emerging trends on how FSM is being organized are discussed. This report complements, with a new focus and in-depth analysis, the study conducted by Rao et al (2016), by trying to answer the central questions -"What is the best way to ensure that FSM is paid for in the long term?" "What arrangements should the key stakeholders make for a successful FSM project?"…”
Section: About the Report -Business Models For Fsm In Indiamentioning
confidence: 96%
See 1 more Smart Citation
“…WLE has explored the technical feasibility and key institutional constraints through a review of 200 case studies across Asia, Africa and Latin America. The research has resulted in a set of promising business models for the safe reuse of human waste, and it is influencing national policies and programs, such as Ghana's fertilizer subsidy program and a new pelletized compost, Fortifer TM , which has been approved for commercial use (Rao et al 2016;Cofie et al 2016). In May 2017, a public-private partnership launched a co-composting plant designed to produce Fortifer TM in Tema, Ghana (IWMI 2017).…”
Section: Recovering Nutrients From Waste and Replenishing Soilsmentioning
confidence: 99%
“…Not only has it been practiced for generations in many countries either formally or informally, but it has also been proposed and tried on a small scale as a green solution for modern cities (Smit and Nasr 1992;Murray and Buckley 2010;Murray et al 2011;EAI 2011). Farmers in West Africa and South India, for example, redirect cesspit truck operators to dump the raw collected fecal sludge on their farm fields to obtain the nutrient-rich manure (Otoo and Drechsel 2018;Rao et al 2016;. Health authorities however are more concerned about the health issues associated with the use of raw fecal matter in food production but field experiments in Ghana have shown that with sufficient solar drying and crop restrictions, these risks can be minimized (Seidu 2010;Keraita et al 2014) and this is even possible in situations where there are limited regulations governing the process.…”
Section: Introductionmentioning
confidence: 99%